A Systematic Review on the Executive Compensation Gap and Its Multiple Impacts on the Company - Malan, Irfah Najihah Basir; Yingkun, Lyu; Kamaruddin, Halim Shukri (Information Management and Business Review, 2023)
In recent years, the public has begun to pay attention to the compensation gap of executives, in such a background of social reality, this researcher conducts a systematic review of the executive compensation gap (horizontal gap and vertical gap) and its impacts on the company through the review and summary of the empirical studies of Scopus Indexed journal articles for the last decade of 2013-2022, then this study figure out the literature trend in this research area in the last decade, summarized how the literature measure executive compensation gap, then reviewed the impact of executive compensation gap can have on company (company performance, risk management, innovation ability, audit fees and other aspects), and at last summarized the findings and put forward the suggestion for future researchers. Such research fills the gap of a systematic review of the executive compensation gap and its impact on companies and provides the company compensation plan maker with practical evidence.